Duodenal Eosinophilia and Gastroparesis: Is there a role? - Sharareh Moraveji; Mohammad Bashashati; Ben Alvarado; Irene Sarosiek; Alireza Torabi; Richard McCallum (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Gastroparesis (GP) is a disorder that affects the motility of the stomach resulting in delayed gastric emptying (GE) without mechanical obstruction and has accompanying symptoms that include nausea, vomiting, early satiety, bloating, and epigastric pain. It was reported that increased eosinophils were identifi ed in the fi rst part of the duodenum in a subset of patients with the entity of functional dyspepsia (FD) and the main symptom of early satiety. It is recognized that approximately 40% of FD patients may also have delayed gastric emptying, termed Idiopathic GP (ID-GP). Therefore, to investigate the  hypothesis that duodenal eosinophilia may be present in patients diagnosed with ID-GP we investigated whether there is any evidence of increased numbers of duodenal eosinophils in patients with the diagnosis of IDGP as compared to diabetic GP (DM-GP) patients and controls who had a normal GE. Methods: Endoscopic biopsies were obtained from the fi rst part of the duodenum in 15 ID-GP and 15 DM-GP patients, all symptomatic and with documented GP based on scintigraphic evidence of >10% retention of a radiolabeled meal at 4 hours. In addition, we studied 18 patients with a normal gastric emptying undergoing endoscopy for miscellaneous indications. None of the GP and controls had any organic GI abnormality. The biopsies were stained with H&E and the eosinophils in intact duodenal villi were counted and averaged in 5 high power fi elds (HPF) by 2 independent experts who were blind to the clinical diagnosis. Results: None of the ID-GP, DM-GP and control patients had any duodenal infl ammation or pathological features of celiac disease. No gastric pathology was detected and the gastric biopsies were negative for H. Pylori. No signifi cant differences were observed in duodenal eosinophil counts among the 3 groups- specifi cally the mean number of eosinophils in the fi rst part of duodenum of control patients was 8.8/HPF (SD 3.9), while this was 11.7/HPF (SD 9.9) in DM-GP and 10.8/HPF (SD 7.3) in ID-GP. Conclusion: Duodenal eosinophils are not increased in ID-GP patients, which would indicate that duodenal eosinophilia does not seem to play a role in the pathophysiology of this disorder nor indicate that there may be a spectrum linking some functional dyspepsia patients to gastroparesis.